Christian ethics : four views - Wilkens, Steve, 1955- (Downers Grove : InterVarsity Press, 2017)
The field of Christian ethics is the subject of frequent conversation as Christians seek to understand how to live faithfully within a pluralistic society. The range of ethical systems and moral philosophies available can be confusing to people seeking clarity about what the different theories mean for everyday life. Christian Ethics: Four Views presents a dialogue between four main approaches to ethics in the Christian tradition. Virtue ethics focuses less on the action itself and more on the virtuous character of the moral agent. A divine command approach looks instead at whether an action has been commanded by God, in which case it is morally right. Natural law ethics argues for a universal, objective morality grounded in nature. Finally, prophetic ethics judges what is morally right in light of a biblical understanding of divine justice and shalom.
Virtue ethics / Brad J. Kallenberg -- Natural law / Claire Brown Peterson -- Divine command theory / John Hare -- Prophetic ethics / Peter Goodwin Heltzel.
Includes index.
Print version record and CIP data provided by publisher; resource not viewed.
Includes bibliographical references and index.
Master record variable field(s) change: 072 - OCLC control number change
Keywords: Christian ethics; Christian ethics; RELIGION / Christian Theology / Ethics; Electronic books